EFEK TEPI KORIDOR JALAN DI HUTAN BUKIT POHEN, CAGAR ALAM BATUKAHU, BALI - Dini Fardila; Sutomo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Road corridor has been known to have an influence on the microclimate and vegetation condition along the forest edge which directly bordered with the road. This study was conducted in order to obtain information regarding the depth of edge influence which can be seen by the changes in microclimate and vegetation condition from forest edge to interior in Pohen Mountain, Batukahu Nature Reserve Bali. Microclimate variables such as light intensity, wind velocity, temperature and relative humidity, and vegetation variables such as basal area, tree height, density and number of species were measured on two 100 m transects perpendicular from forest edge to interior. The correlation between microclimate and vegetation condition with distance from the road was analyzed by using MANOVA and ANOVA. The depth of edge influence was estimated by using Principal Component Analysis (PCA) ordination. Microclimate showed significant correlation with distance from the road to forest interior (r > 0.5, p < 0.05). Light intensity, temperature and wind velocity tends to decline as we move towards the forest interior and the reverse was true for the relative humidity. Microclimate gradient changed sharply until it reached the distance of 40 m from the forest edge. For vegetation parameter only the height of trees which was signifi cantly correlated with the distance from the road. PCA analysis showed that the depth of edge influence for the microclimate condition was clearly showed up until 40 m from the road. This result suggests that forest buffer area with minimum width of 40 m is needed to protect the forest interior of Pohen Mountain from the exposed microclimatic condition of the edge area.